REGULATORY AND LEGAL FRAMEWORK FOR THE DEVELOPMENT OF FINANCIAL SERVICES OF NON-BANK CREDIT INSTITUTIONS IN UZBEKISTAN (World Economics and Finance Bulletin, 2024)
This article describes the methodological aspects and regulatory framework for improving the quality of financial services of non-bank credit institutions in Uzbekistan. The author's approaches and proposals to overcome them are also presented, as well as existing problems related to the prospect that non-bank credit institutions will contribute to economic development by providing access to financing for those who cannot receive it from traditional banks, and that entrepreneurship support, which is becoming important in the development of small and medium-sized businesses, It will serve to create jobs and improve the lives of the population
Keywords: foreign countries; non-bank credit organizations; Microfinance